Sexual reproduction, larval morphology and behaviour in demosponges from the southwest of the Netherlands. In: Vacelet J., Boury-Esnault N. (eds) Taxonomy of Porifera from the N.E. Atlantic and the Mediterranean Sea. - Wapstra, M.; van Soest, R.W.M. (NATO Advanced Science Institutes Series G, Ecological Sciences, Springer, Heidelberg, 1987)
The reproductive periods of sponge species from the SW of The Netherlands were determined. Morphological characteristics of the larvae of the recently described Haliclona xena and Mycale micracanthoxea are given. More detailed information is included on the previously described larvae of Halichondria panicea, Halichondria bowerbanki, Hymeniacidon perlevis, Haliclona oculata, Haliclona rosea, Acervocha1ina loosanoffi and Dysidea fragilis. Morphological changes in sponge larvae during their free life are described. Furthermore an overview of known larval descriptions is included along with a discussion of the taxonomic value of larval features.
Proceedings of the 2nd Workshop on Atlanto-Mediterranean Sponge Taxonomy